2018
DOI: 10.18512/1980-6477/rbms.v17n1p76-90
|View full text |Cite
|
Sign up to set email alerts
|

Resposta Do Milho Safrinha À Adubação Em Duas Épocas De Semeadura

Abstract: RESUMO -neste trabalho, objetivou-se avaliar a resposta do milho à adubação nPK, em semeadura realizada nos meses de janeiro e fevereiro, sucedendo a cultura da soja, em rio verde-go. o experimento foi conduzido em delineamento de blocos casualizados, num esquema fatorial 4x2, constituído por quatro opções de adubação nPK na semeadura, com ou sem adubação nitrogenada de cobertura. Foram cultivados os híbridos P 30F53 Yh e dKB 310 Pro, no primeiro e segundo anos, respectivamente, e coletados os dados de altura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…Nitrogen fertilization often results in yield gains in off-season corn crops (Mar et al, 2003;Soratto et al, 2010;Simão et al, 2018), but different studies have reported variable response patterns to the amount and time of N application. In Dourados, in state of Mato Grosso do Sul, Brazil, Mar et al (2003) obtained an increase of 1,497 kg ha -1 grains by applying 30 kg ha -1 N, corresponding to an increase of 48.5%, which reached 114.4% for a N rate of 120 kg ha -1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen fertilization often results in yield gains in off-season corn crops (Mar et al, 2003;Soratto et al, 2010;Simão et al, 2018), but different studies have reported variable response patterns to the amount and time of N application. In Dourados, in state of Mato Grosso do Sul, Brazil, Mar et al (2003) obtained an increase of 1,497 kg ha -1 grains by applying 30 kg ha -1 N, corresponding to an increase of 48.5%, which reached 114.4% for a N rate of 120 kg ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the Cerrado biome, off-season corn is grown in several different subregions, sowed between January and March, encompassing a wide range of soil and climate conditions (Nóia Júnior & Sentelhas, 2019a), which makes it difficult to reach a consensus on the decision criteria to recommend N fertilization. The uncertain climate conditions at the end of the rainy season affect both the corn yield potential (Simão et al, 2018) and the cycling of N from the residue of the preceding crop (Rossi et al, 2013), normally soybean [Glycine max (L.) Merr.]. The intensity of these interferences varies between years and crop sites, hindering the establishment of fertilizer recommendations applicable to all situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Simão et al (2018), the sowing season defines the water availability conditions and influences the second-crop corn yield, so that the earlier sowing favors its yield. Corn was sown on March 16 in the 2018 growing season and March 6 in the 2019 growing season.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of sowing time on maize grain yield in second crop is directly related to rainfall regime. Better distribution of rainfall is overriding, mainly in the final stages of vegetative development and at the beginning of reproductive development (Simão et al, 2018). Cardoso et al (2004) evaluated 12 maize sowing times from January to April, with and without water limitation.…”
Section: Variance Analysismentioning
confidence: 99%